Antioxidant and antibacterial properties of Citrus paradisi barks extracts during turkey sausage formulation and storage. Issue 4 (October 2015) - Sayari, Nadhem; Sila, Assaâd; Balti, Rafik; Abid, Emna; Hajlaoui, Kamel; Nasri, Moncef; Bougatef, Ali
Abstract: Antioxidant and antibacterial properties of Citrus paradisi fruit barks (CPFB) extract was evaluated in turkey sausage formulation and storage. The CPFB water extract contained a high amount of total phenolics and flavonoids (118±4 mg GAE g −1 dried extract and 794±8.7 mg QE g −1 dried extract, respectively) and showed important antioxidant and antibacterial activities in all assays used. The capacity of the water extract of CPFB to delay lipid oxidation in sausages was evaluated at the level of 2.5 g kg −1 turkey sausage. Water extracts from CPFB showed a higher antioxidant activity than sodium lactate. Microbial growth was monitored regularly during 14-day storage of sausages at 4 °C. The number of microorganisms decreased significantly ( p <0.05) when CPFB water extract was added to the sausage. Our results show that the addition of herbal extracts can minimize lipid oxidation and improve microbiological stability during the formulation and storage of turkey sausage.